Planning Analysis of Asphalt Porous Mixture Based on Fly Ash Waste as Filler Substitution - Gusty, Sry; Irmawan, Irmawan; Desi, Natsar (ASTONJADRO, 2023)
In relation to the development of the quality of the transportation system, road pavement technology will gradually develop and be updated in terms of the quality of the transportation infrastructure currently being developed by porous asphalt. Porous asphalt is an asphalt mixture that is designed to have a higher porosity than other types of pavement. it is obtained because the porous asphalt mixture uses a smaller proportion of fine aggregate than other mixtures. In addition to asphalt, there are aggregates both coarse and fine and filler is one of the components in a road pavement construction that has a big role. In order to increase its stability, the use of fine fractions including filler in the mixture proportion should be more. Class C coal fly ash is one of the non-organic and non-plastic materials that can be used as a filler in porous asphalt mixtures and is expected to increase its strength. The purpose of this study was to analyze the effect of using flyash on a porous asphalt mixture on the value of the marshall characteristics and the value of weight loss. The results of this study discuss the marshall test on variations in coal flyash waste 0%, 2%, 3%, 4%, 5%, and 6% using the REAM specification, for the VMA value the percentage of coal flyash waste all meets the specifications specified. has been required, for the VIM value only the percentage of 4% that meet the specifications and 0%, 2%, 3%, 5%, and 6% do not meet the required specifications. For the stability value, the percentage of coal flyash waste 2%,3%,4% met the specifications, while 0%,5%, and 6% did not meet the specifications. For the flow value, the percentage of coal flyash waste 5% did not meet the specifications, while 0%,2%,3%,4%, and 6% had met the required specifications. And for the value of VFB and MQ the percentage of coal flyash waste does not meet the required specifications. Based on the results of the REAM cantabro test, the percentage of coal flyash waste 0% and 2% did not meet the specifications, while 3%,4%,5%, and 6% met the predetermined specifications, namely the maximum weight loss value of 20%.